2023
DOI: 10.1002/adfm.202303043
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Phenolic Pectin Hydrogels for Saliva Substitute and Oral Patch

Abstract: Oral disease is one of the most common conditions worldwide, negatively affecting general health, reducing the quality of life, and often developing into systemic illness. However, the design of therapeutic agents for oral diseases is challenging due to various unique features of the oral cavity, including its wet and dynamic environment and curved shape. Herein, the development of highly biocompatible mucoadhesive functional hydrogels for oral applications is reported, generated by introducing bio‐inspired ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Mucin, the main component of mucus, is produced by epithelial tissue and secreted onto the mucosal surface to preserve a healthy oral environment. 15,18 So, the adhesion mechanism of the C-P-G film was elucidated by investigating the interaction of C-P-G with mucin. The results of atomic force microscopy (AFM), the average surface roughness (Ra), and dynamic light scattering (DLS) revealed that aggregates formed when mucin co-mingled with C-P-G, suggesting a high affinity between C-P-G and mucin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucin, the main component of mucus, is produced by epithelial tissue and secreted onto the mucosal surface to preserve a healthy oral environment. 15,18 So, the adhesion mechanism of the C-P-G film was elucidated by investigating the interaction of C-P-G with mucin. The results of atomic force microscopy (AFM), the average surface roughness (Ra), and dynamic light scattering (DLS) revealed that aggregates formed when mucin co-mingled with C-P-G, suggesting a high affinity between C-P-G and mucin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite widespread exploration of mussel-inspired formulations for strong adhesion in wet environments, 15,34 they often bring about instability due to the introduction of unstable compounds, organic solvents, and toxic cross-linking agents. These factors contribute to unpredictable safety issues, limiting their clinical translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this goal, Seung-Woo Cho et al employed pyrogallol in pectin polymers to construct mucoadhesive polymer hydrogels. 129 Mucoadhesive strength was achieved by covalent bonding including Michael addition and Schiff reactions, and non-covalent interactions including hydrogen bonding, hydrophobic interactions and π–π stacking between pyrogallol and mucin proteins. After spraying onto a rat tongue, hydrogels formed in situ and adhered onto the tongue tightly regardless of vigorous PBS wash.…”
Section: Wet-adhesive Polymeric Materials To Overcome the Highly Mova...mentioning
confidence: 99%
“…Pectin hydrogels find valuable pharmaceutical applications owing to their biocompatibility, controlled drug release capabilities ( Güner et al, 2021 ), and versatility in formulation. These hydrogels are employed in oral drug delivery systems ( Choi et al, 2023 ), where they protect sensitive drugs from the harsh gastric environment and enable controlled release in the intestinal tract, enhancing drug bioavailability and patient compliance. In addition, pectin hydrogels are used for targeted and sustained drug delivery to specific sites ( An et al, 2021 ), rendering them suitable for treating various ailments, including gastrointestinal disorders and chronic diseases.…”
Section: Pectin In Pharmaceutical Formulationsmentioning
confidence: 99%